STORYTELLING DAN DEMONSTRASI MENINGKATKAN PENGETAHUAN, SIKAP, DAN TINDAKAN CUCI TANGAN PAKAI SABUN PADA ANAK - Lestari, kustati Budi; Putri, Aprilia Wulandari (Prodi Ilmu Keperawatan, Fakultas Ilmu Kesehatan, UIN Syarif Hidayatullah Jakarta, 2024)
Background: School children do many activities using their hands, so hands are important in cleanliness. Improper handwashing behaviour with soap is still high in children. This study aimed to determine the effect of storytelling and demonstration on increasing knowledge, attitudes, and actions of handwashing with soap. Method: This quantitative research uses a pre-experimental design with one group pre-test post-test design method. The sample amounted to 58 people with simple random sampling techniques. Data collection using questionnaires compiled by researchers has been tested for content validity on pediatric nursing experts and has a Croanbach's Alpha value of 0.860, data analysis using Wilcoxon and Mc Nemar tests. Results: The results of the study found a significant influence of health education with storytelling and demonstration methods on increasing knowledge, attitudes, and actions with p-value = 0.000 < 0.05. Conclution: Health education with storytelling methods and demonstrations about handwashing with soap can be given to children because by telling stories and practices children can more easily understand the message conveyed. Teachers are required to be creative and smart in telling stories so that the message given is on target.